Accumulation of NACP/α-synuclein in Lewy body disease and multiple system atrophy. Issue 5 (1st May 2000) - Shoji, Mikio; Harigaya, Yasuo; Sasaki, Atsushi; Uéda, Kenji; Ishiguro, Koji; Matsubara, Etsuro; Watanabe, Mitsunori; Ikeda, Masaki; Kanai, Mitsuyasu; Tomidokoro, Yasushi; Shizuka, Masami; Amari, Masakuni; et al.
Abstract : OBJECTIVES: NACP/α-synuclein is an aetiological gene product in familial Parkinson's disease. To clarify the pathological role of NACP/α-synuclein in sporadic Parkinson's disease and other related disorders including diffuse Lewy body disease (DLBD) and multiple system atrophy (MSA), paraffin sections were examined immunocytochemically using anti-NACP/α-synuclein antibodies. METHODS: A total of 58 necropsied brains, from seven patients with Parkinson's disease, five with DLBD, six with MSA, 12 with Alzheimer's disease, one with Down's syndrome, one with amyotrophic lateral sclerosis (ALS), three with ALS and dementia, one with Huntington's disease, two with progressive supranuclear palsy (PSP), one with Pick's disease, one with myotonic dystrophy, and three with late cerebellar cortical atrophy (LCCA), and 15 elderly normal controls were examined. RESULTS: In addition to immunoreactive Lewy bodies, widespread accumulation of NACP/α-synuclein was found in neurons and astrocytes from the brainstem and basal ganglia to the cerebral cortices in Parkinson's disease/DLBD. NACP/α-synuclein accumulates in oligodendrocytes from the spinal cord, the brain stem to the cerebellar white matter, and inferior olivary neurons in MSA. These widespread accumulations were not seen in other types of dementia or spinocerebellar ataxia. CONCLUSION: Completely different types of NACP/α-synuclein accumulation in Parkinson's disease/DLBD and MSA suggest that accumulation is a major step in the pathological cascade of both diseases and provides novel strategies for the development of therapies.